Synthesis and Spectral Studies of Mercury(II) Complexes of 4-Bromobenzoylmethylenetriphenylphosphorane - JAVAD SABOUNCHEI, SEYYED; DADRASS, A.R. (Asian Journal of Chemistry, 2010)
The new α-phosphorus ylide of (4-bromobenzoylmethylenetriphenylphosphorane) (BBPPY) (1) is prepared by the reaction of 2,4'-bromoacetophenone with triphenyl phosphine in chloroform as solvent. The mercury(II) complexes of the type (BBPPY· HgCl2) (2), (BBPPY·HgBr2) (3), (BBPPY· HgI2) (4) and (BBPPY·Hg(NO3)2 (5) are prepared by the reaction of BBPPY with mercury(II) halides and nitrate in moderate to good yields.